Eksplorasi Peranan Strategi Metakognisi dalam Kemampuan Membaca Teks Multimodal Bahasa Inggris Pada Siswa di Daerah Rural - Manalu, Theresia (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2024)
Several studies affirmed a close relationship between the positive reading output and the level of metacognitive reading strategies activation of students. This study reported an investigation the exploration of students’ metacognitive reading strategies role in reading different multimodal texts. For this purpose, 54 EFL senior high school students from a rural area in North Sumatera participated in this study. The findings showed that the EFL students performed high preference of the problem-solving strategies in both texts. Interestingly, the practical activation of students’ metacognitive reading strategies during think-aloud session was captured not only from students’ utterances but also from their behavioral and gestural actions. The findings then evidenced on the similarities and differences of metacognitive reading strategies of EFL students. Meanwhile, writing summary strategy was only found in students when reading audio-visual text. As a result, the overall findings warrant explicit reading strategy instructions that concern the authenticity of texts in the form of multimodal texts to stimulate students’ metacognitive awareness and improve students’ reading proficiency level.